Mental Health in Lifestyle Medicine: A Call to Action. Issue 1 (January 2022) - Merlo, Gia; Vela, Alyssa
Mental health symptoms are pervasive, with 1 in 5 American adults experiencing a mental disorder. Poor mental health is associated with a significant global cost burden, from disability to economic impacts. The field of lifestyle medicine, which emphasizes the role of lifestyle factors in the onset and treatment of disease and well-being, is well suited to address mental health. More recently, there has been attention to the need to incorporate mental health into the field of lifestyle medicine and to attend to the bidirectional role of mental health and lifestyle. Thus, there is a critical opportunity for the field of lifestyle medicine to incorporate mental health into each of the foundational pillars (diet, exercise, substance use, psychological well-being/stress, relationships, sleep) while also specifically targeting lifestyle interventions for populations with mental disorders. The current article provides a framework for the role of mental health within lifestyle medicine by addressing the scope of the problem, clarification regarding mental health, and areas of practice (ie, psychiatry), and providing an overview of the relevant mental health literature for each pillar. This article serves as a call to action to explicitly address and include mental health within all aspects of lifestyle medicine research and practice.